KERAGAMAN DAN KEKERABATAN KULTIVAR JAGUNG (Zea mays L.) LOKAL ASAL PULAU KISAR KABUPATEN MALUKU BERDASARKAN KARAKTER FENOTIP - Hermalina Sinay; Estri Laras Arumingtyas; Nunung Harijati; Serafinah Indriyani (Program Studi Pendidikan Biologi FKIP Unpatti, 2016)
Background: The relationship of plant kinship can be done through the identification of the phenotype character that is the character that appears on the individual or plant organism that can be both quantitative and qualitative. The purpose of this research is to know the diversity and kinship of corn cultivar from Kisar Island Regency of Maluku Southwest of Maluku Province based on phenotype character. Methods: The genetic material used was six local corn cultivars and one comparative variety. The six local corn cultivars are Red ruby with a brown cob, Blood red corn, Sticky, Ripe yellow, Deep yellow, and White, while the varieties are Srikandi varieties. To know the effect of cultivars and corn varieties on phenotypic diversity, variant analysis with Statistica Analytical System (SAS version 9.0) was used. To know the character that gives the greatest contribution to the diversity of cultivar phenotype and corn varieties, the main component analysis is done. To know the kinship among corn cultivars based on phenotypic character, gross analysis (cluster analysis) with hierarchy method is performed. The main component analysis and gameplay analysis was performed using SPSS version 18.0 computer program. Results: The results of variance analysis showed a significant effect of maize cultivar on phenotypic diversity. Characters that contribute to the diversity of the corn cultivar phenotype are the proline level, the weight of cobs without harvesting at harvest, the weight of cobs without dryness of the oven, the weight of the cobs at 12% moisture content, the unleaded cobs at 12%, the diameter of the ear, the number of seeds per ear, the number of rows of beans per ear, the number of leaves, and the length of the leaf. The results of Euclidean and Euclidean girder analysis show that the local yellow cultivars are in one group alone and have a low similarity with other local corn cultivars as well as the Srikandi-based varieties based on their phenotypic characters. Conclusion: There is a variety of phenotypes of local corn cultivars and varieties of Srikandi compounds grown on Kisar Island of Southwest Maluku Maluku Province.